A retrospective overview of Journal of Enterprise Information Management using bibliometric analysis. Issue 2 (30th April 2021) - Donthu, Naveen; Kumar Badhotiya, Gaurav; Kumar, Satish; Soni, Gunjan; Pandey, Nitesh
Abstract : Purpose: Journal of Enterprise Information Management ( JEIM ) is a leading journal that publishes studies on applied information management relevant to industry personals, academicians and researchers. This study uses bibliometric tools to present a retrospective analysis of the journal's outcomes. Design/methodology/approach: The authors applied bibliometric tools for analysing the impact, topic coverage, renowned authors with affiliation, citation, methodology and analysis of the JEIM corpus. Additionally, they used bibliographic coupling to develop a graphical visualisation and analyse the journal's thematic evolution. Findings: With 16 yearly articles, JEIM contributed 656 research articles on various themes. The major themes that have come to define the JEIM over this time include information and systems, supply chain management, manufacturing resource planning, communication technologies and small- to medium-sized enterprises. Empirical methodology, quantitative techniques with descriptive analysis and regression methods are the most preferred. The article's primary research purpose shows the majority of theory-verifying articles. Co-authorship analysis reveals that the single-author trend is decreasing and the journal now has articles with international collaborations. Originality/value: This study is the retrospective analysis of the JEIM, which is useful for aspiring contributors and the journal's editors.